2010
DOI: 10.1113/jphysiol.2009.182147
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological identification of glucose-sensing neurons in rat nodose ganglia

Abstract: The vagal afferent system is strategically positioned to mediate rapid changes in motility and satiety in response to systemic glucose levels. In the present study we aimed to identify glucose-excited and glucose-inhibited neurons in nodose ganglia and characterize their glucose-sensing properties. Whole-cell patch-clamp recordings in vagal afferent neurons isolated from rat nodose ganglia demonstrated that 31/118 (26%) neurons were depolarized after increasing extracellular glucose from 5 to 15 mm; 19/118 (16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 55 publications
2
71
1
1
Order By: Relevance
“…However, diazoxide had no effect on the FA-induced increase in cytosolic calcium in nodose neurons. This result is not due to the absence of this channel in nodose neurons, since effects of glucose on glucoseexcited nodose neurons have been shown to be mediated by the K ATP channel (15). Our finding that FA effects in nodose neurons are independent of this channel suggests that these effects do not require changes in ATP levels in these neurons.…”
Section: Discussionsupporting
confidence: 56%
“…However, diazoxide had no effect on the FA-induced increase in cytosolic calcium in nodose neurons. This result is not due to the absence of this channel in nodose neurons, since effects of glucose on glucoseexcited nodose neurons have been shown to be mediated by the K ATP channel (15). Our finding that FA effects in nodose neurons are independent of this channel suggests that these effects do not require changes in ATP levels in these neurons.…”
Section: Discussionsupporting
confidence: 56%
“…Each esophagus received three injections. Four nodose ganglia (2 from each animal) were collected 10 days later and processed for whole cell patch-clamp recordings, as we previously described (12). Briefly, nodose ganglia from normal guinea pigs were minced in a 35-mm culture dish (containing Ca 2ϩ -and Mg 2ϩ -free Hanks' balanced salt solution with penicillin and streptomycin) and then placed in a 1.5-ml centrifuge tube containing digestion buffer (dispase II and collagenase IA, 1 mg/ml; Roche Applied Science).…”
Section: Methodsmentioning
confidence: 99%
“…In general, in glucose-excited neurons, glucose metabolism leads to KATP channel closure, triggering membrane depolarization, whereas in glucose-inhibited neurons, the inhibitory effect of elevated glucose is mediated by an ATP-independent K + channel. 30 Some studies have demonstrated that glucose-inhibited neurons have been found in some CNS regions, including NTS, DMV and hypothalamus. [30][31][32] The mechanism of glucoseinduced neuronal inhibition is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…30 Some studies have demonstrated that glucose-inhibited neurons have been found in some CNS regions, including NTS, DMV and hypothalamus. [30][31][32] The mechanism of glucoseinduced neuronal inhibition is not well understood. 38 In general, increased blood glucose level, possibly via aforesaid inhibitory mechanisms may have contributed to seizure severity reduction, although as said, details are less understood.…”
Section: Discussionmentioning
confidence: 99%